Studing Effect of Temperature on Some Mechanical Properties of Single And Hybrid Composites - Abdullah, M.Z.; Al-Sarraf, A. R.; Dhiaa, B. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research,we are studied impact strength, bending and compression strength of composites including the epoxy resin as a matrix , with gawaian red wood flour ,Russian white wood flour ,glass powder and rock wool fibers as reinforcement materials with volume fraction (20%) for all samples,and compared them in different conditions of temperatures. The results have shown that the impact strength increased with the reinforcement with (particles and fibers),and at high temperatures for all samples prepared,and also observed an increase in elasticity coefficient of epoxy composites filled with (different particles) and decreased in elasticity coefficient of epoxy composites filled with (particles and fibers) , on the other hand the elasticity coefficient of all the samples prepared decreased at high temperatures,and increased in compression strength of all samples at room temperature ,but at high temperatures compression strength of all samples decreased.